2014
DOI: 10.1097/bsd.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Patients With Spondylodiscitis and Neurological Deficits Caused by Spinal Epidural Abscess (SEA) is a Predictor of Clinical Outcome

Abstract: Surgical treatment of patients with spondylodiscitis and neurological deficits caused by SEA is a predictor of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Gupta et al showed that surgical treatment often fails within the first 6 months, whereas the failure rate at 2 years is similarly high to that at 5 and 10 years (5). Rossbach et al demonstrated that the prognosis of neurological deficits, independent of the surgical approach used, is improved by 1 or 2 Frankel scores (measurement of spinal cord function) if decompression of the causal epidural abscess is achieved (29). On the whole, back pain often persists irrespective of the selected treatment approach.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al showed that surgical treatment often fails within the first 6 months, whereas the failure rate at 2 years is similarly high to that at 5 and 10 years (5). Rossbach et al demonstrated that the prognosis of neurological deficits, independent of the surgical approach used, is improved by 1 or 2 Frankel scores (measurement of spinal cord function) if decompression of the causal epidural abscess is achieved (29). On the whole, back pain often persists irrespective of the selected treatment approach.…”
Section: Resultsmentioning
confidence: 99%
“…The descriptive RCS by Rossbach et al presented the results of a cohort of patients with spondylodiscitis and a subgroup in which the spondylodiscitis was complicated by a spinal epidural abscess [32]. Patients with a neurological deficit caused by an epidural abscess had a statistically significant better prognosis than patients with other causes of neurological deficit [32] (Table 6). …”
Section: Outcomes Of Surgical Treatmentmentioning
confidence: 99%
“…Similarly, four included study populations consisted of 0.9-13.5 % children and adolescent patients [4,6,27,34]. Additionally 3 other studies contained patients between 16 and 18 years of age; however, the number of these patients is not described [32,35,36]. A total number of 31 children and adolescents have described in the included studies and represent 1.3 % of the study population in this review [4,6,27,34].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations